COVID 2019 asymptomatic infections across the World- can it be a Time Bomb for Future Pandemic Recurrence? A Systematic Review of surveillance strategies - Sanjeev Davey; Rajesh Jain; Anuradha Davey (Archives of Community Medicine and Public Health - Peertechz Publications, 2020)
Background: Covid 2019 Infection can be considered a disease typically following Ice berg Phenomenon, where actual large no of submerged cases are inside and can become threat to human beings as immunity development to SARS -CoV-2 cannot be forever. Studies across the World have suggested that out of many important research questions- the problem of asymptomatic and presymptomatic virus shedding is one of the most gray area in management of COVID 20019 pandemic across the world.  Objective: Unrecognized threat of Incubatory carriers as well as asymptomatic cases becoming a re-infection pool to Global Community can be very dangerous for whole world. So a strategy for further Management of asymptomatic and presymptomatic CORONA +ve cases needs urgent appraisal, if we have to prevent future recurrence of COVID 2019 Pandemic. That why a systematic research is crucial in this regard, as attempted by authors in this article.  Material & methods: As per PRISMA(2009) guidelines protocol, search of various kinds of studies in any form ;using five key search words: 'Asymptomatic', "Presymptomatic" "COVID 2019 Infection Surveillance, Pandemic, Recurrence " was done in all health related websites of Google, PubMed, EMBASE, MEDLINE, Global Health, , Biomed‑Central, Web of Science, Cochrane Library, world library ‑ World‑Cat, from 1 January, 2020 to 25th April 2020 for systematic‑review, followed by Meta-Analysis.  Results: Out of wide variety of 31 studies available in literature related to this topic,20 were found to be eligible for issues synthesis, from which 2 crucial themes of Surveillance of Symptomatics and Asymptomatic & Presymptomatics emerged. The Symptomatics surveillance was good in the form of Isolation and Quarantine across the World; but the real problem was of Asymptomatic post discharge surveillance, which was only in nascent stage in many countries across the world including developing countries such as India.  Conclusion: Lack of asymptomatic post discharge surveillance may cause a real havoc in future, if no strategy is chalked out by governments across the World, leading to possible recurrence of COVID 2019 Pandemic. However authors suggest more future research studies, before we can say it very definitively that it will certainly happen.